2004
DOI: 10.1093/her/cyg014
|View full text |Cite
|
Sign up to set email alerts
|

Differences in physical activity levels between urban and rural school children in Cyprus

Abstract: This study attempted to examine differences in physical activity levels between urban and rural primary school children. The sample consisted of 256 Greek-Cypriot children and their parents from two schools representing urban areas and three schools representing rural areas. Children's activity levels were assessed for 4 weekdays in the winter and for 4 weekdays in the summer using a pedometer (DW-200; Yamax, Tokyo, Japan). Daily step counts were used to describe children's activity levels. Parents completed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
112
3
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 30 publications
12
112
3
9
Order By: Relevance
“…Another environmental factor of importance is population density of the child's living area, children and adolescents from rural districts tend to spend more time doing outdoor games, sports and domestic chores, whereas children in urban areas spend more time in organized sports, in designated play areas or specialized institutions where they are transported by an adult to play and be physically active [29,41,42]. The Children's Assessment of Participation and Enjoyment (CAPE) is a selfreported measure of participation assessing the number of leisure activities done and the intensity of the involvement [28,43].…”
Section: Introductionmentioning
confidence: 99%
“…Another environmental factor of importance is population density of the child's living area, children and adolescents from rural districts tend to spend more time doing outdoor games, sports and domestic chores, whereas children in urban areas spend more time in organized sports, in designated play areas or specialized institutions where they are transported by an adult to play and be physically active [29,41,42]. The Children's Assessment of Participation and Enjoyment (CAPE) is a selfreported measure of participation assessing the number of leisure activities done and the intensity of the involvement [28,43].…”
Section: Introductionmentioning
confidence: 99%
“…In a study performed in children attending the elementary school in Cyprus, it was found that children living in rural areas were more active in summer months and children living in urban areas were more active in winter months (41). Since our study was performed in May, it may be predicted that seasonal effect would be minimal.…”
Section: Limitationsmentioning
confidence: 82%
“…There are also studies showing that physical activity level shows seasonal variability (41). In a study performed in children attending the elementary school in Cyprus, it was found that children living in rural areas were more active in summer months and children living in urban areas were more active in winter months (41).…”
Section: Limitationsmentioning
confidence: 99%
“…Children who lives in rural area experienced more actvities than those who lives in urban areas. Children who lives in positive environment have tendencies to behave negative behaviour (Loucaides et al, 2004;David-Ferdon, & Hertz. 2007)).…”
Section: The Relationship Of Environmental Influence and Negative Behmentioning
confidence: 99%